Minimum Lap Time Simulation Framework: Active Aerodynamics and Torque Distribution - Rijns, Steven; Siampis, Efstathios; Teschner, Tom-Robin; Blackburn, Kim; Brighton, James (Cranfield University, 2025)
The Minimum Lap Time Problem (MLTP) simulation framework is an optimisation tool designed to simultaneously optimise a vehicle’s trajectory, control inputs, and selected design parameters to achieve the fastest possible lap time for a given track. It employs an optimal control approach with direct collocation, leveraging CasADi and IPOPT to define and solve the optimisation problem. The MLTP framework builds on the original work by Zarzuelo and Siampis [1] and the extensions by Jiménez et al. [2], expanding its capabilities with a more advanced vehicle model and enhanced optimisation functionalities, including active aerodynamics and active torque distribution configurations. The optimisation framework is applied to the DrivAer hp-F high-performance vehicle model and has been tuned for the Circuit de Barcelona-Catalunya. It includes design optimisation parameters, such as the distribution of drive torque, brake torque, and roll stiffness, as well as a nominal tyre load shift parameter to analyse tyre characteristics. The MLTP framework has a modular structure, making it a versatile tool for broader applications in vehicle performance optimisation. It enables adaptation to different vehicles and tracks while allowing extensions such as alternative vehicle models, aerodynamic concepts, and design parameters. Users applying it to new scenarios should establish new initialisation cases and re-tune optimisation parameters to ensure viable solutions. This dataset is associated with the following publications: Rijns, S., Teschner, T. R., Blackburn, K., Siampis, E., & Brighton, J. (2024). Optimising Vehicle Performance with Advanced Active Aerodynamic Systems [In Review]. Advanced Vehicle Engineering Centre, Cranfield University. Rijns, S., Teschner, T. R., Blackburn, K., Siampis, E., & Brighton, J. (2024). Performance Optimisation of High-Performance Vehicles with Active Aerodynamics and Active Torque Distribution Capabilities [In Review]. Advanced Vehicle Engineering Centre, Cranfield University. References: [1] Adrián Zarzuelo, Efstathios Siampis (2022). MLTP (https://www.mathworks.com/matlabcentral/fileexchange/119398-mltp), MATLAB Central File Exchange. [2] Jiménez Elbal, A., Zarzuelo Conde, A., & Siampis, E. (2024). Simultaneous Optimisation of Vehicle Design and Control for Improving Vehicle Performance and Energy Efficiency Using an Open Source Minimum Lap Time Simulation Framework. World Electric Vehicle Journal, 15(8), 366. https://doi.org/10.3390/wevj15080366
Keywords: Minimum Lap Time Problem; Vehicle Performance; Performance Optimisation; Active Aerodynamics; Active Torque Distribution; Vehicle Dynamics